Synthesis of Some New Pyrazolines - A.J. AL-Hamdany; A.M. Hamdy (College of Education for Pure Sciences, 2006)
The present work includes the preparation of a series of substituted chalcones ( NO2 , Me , OMe , Cl ) and condensation of these chalcone with a series of prepared aromatic and aliphatic acid hydrazides in a basic medium to afford the new pyrazolines . Physical and spectral methods were used to confirm the structures .